ANALISA HASIL PERFORMA PENGERINGAN PADA MESIN PENGASAP DAGING IKAN DENGAN SISTEM TERTUTUP - Afandi, Akhmad (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2022)
Research has been carried out on analyzing the results of drying performance on fish meat drying machines with a closed system which aims to determine the level of water content reduction in fish meat after the smoking process. In the design of the fish meat smoking machine, testing is carried out at a temperature of 50oC to 70oC to calculate heat, thermal efficiency, moisture content, and smoking time. So with this machine, the smoking process will be more hygienic and efficient than conventional smoking. The results of calculations and discussions show that the rate of heat energy entering the smoking rack is 996 watts, and the rate of heat energy of vaporization is 154.71 watts. Thermal efficiency is obtained from the ratio of heat energy and heat energy rate of vaporization of 15.53%. From the experimental results, the final water content of grouper fish was 46.67%, baronang fish 45%, tuna fish 50%, and lemuru fish 40%.